2000
DOI: 10.1128/aem.66.6.2605-2612.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Survival Rates of Human-Derived Probiotic Lactobacillus paracasei and L. salivarius Strains during Heat Treatment and Spray Drying

Abstract: Spray drying of skim milk was evaluated as a means of preserving Lactobacillus paracasei NFBC 338 and Lactobacillus salivarius UCC 118, which are human-derived strains with probiotic potential. Our initial experiments revealed that NFBC 338 is considerably more heat resistant in 20% (wt/vol) skim milk than UCC 118 is; the comparable decimal reduction times were 11.1 and 1.1 min, respectively, at 59°C. An air outlet temperature of 80 to 85°C was optimal for spray drying; these conditions resulted in powders wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
288
1
16

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(327 citation statements)
references
References 25 publications
22
288
1
16
Order By: Relevance
“…This strain was identified as Lactobacillus paracasei according to 16S rRNA sequencing. Interestingly, this strain exhibited the same PFGE pattern as the probiotic strain Lactobacillus paracasei NFBC 338 (Figure 1c) (Gardiner et al, 1998(Gardiner et al, , 2000Desmond et al, 2005). This was further confirmed by plasmid profiling (Figure 1d).…”
Section: Resultssupporting
confidence: 66%
“…This strain was identified as Lactobacillus paracasei according to 16S rRNA sequencing. Interestingly, this strain exhibited the same PFGE pattern as the probiotic strain Lactobacillus paracasei NFBC 338 (Figure 1c) (Gardiner et al, 1998(Gardiner et al, , 2000Desmond et al, 2005). This was further confirmed by plasmid profiling (Figure 1d).…”
Section: Resultssupporting
confidence: 66%
“…bulgaricus or lactis have an advantage in withstanding higher temperatures during processing and storage (Gardiner et al, 1998;Gardiner et al, 2000;Rodtong and Tannock, 1993;Drake et al, 1996). For instance, L. paracasei NFBC 338 survived significantly better that L. salivarius UCC 118 at similar spray-drying conditions, which may be attributed to the greater thermal tolerance of L. paracasei compared to L. salivarius (Gardiner et al, 2000). Furthermore, it has been shown that B. animalis subsp.…”
Section: Important Parameters Affecting Microencapsulationmentioning
confidence: 96%
“…The drying process causes this solution to shrink into a pure polymer envelope enclosing the core material. Spray drying can be used as a cost-effective method to produce large quantities of probiotic cultures when critical parameters such as the type of atomization, air pressure and outlet-air temperature have been controlled (Gardiner et al, 2000;Champagne and Møllgaard, 2008). Different polysaccharides were used as the matrix and the nozzle temperature of the spray dryer as well as the water activity of the microcapsules had an important impact on the survival of probiotic bacteria.…”
Section: Freeze Drying and Spray Dryingmentioning
confidence: 99%
“…It was assumed that probiotics were encapsulated in the dried samples. Gardiner et al (2000) had similar observation and established the encapsulation of bacterial cells by confocal scanning laser microscopy technique. Skim milk had individual particles but with uniform appearances and surfaces (Figure 3(a)).…”
Section: Spray-dried Lactobacillus Rhamnosus Ggmentioning
confidence: 97%
“…Although there is variability in the minimum recommended levels of probiotics in foods (Charteris et al, 1998), an official standard requiring a minimum of at least 10 7 live micro-organisms/g or ml have been introduced by several food organizations (IDF, 1992;Ishibashi and Shimamura, 1993). Therefore, from a commercial point of view, an inexpensive method for large-scale production of cultures containing high levels of viable probiotic cells in a form suitable for product application is highly desirable (Gardiner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%